Impact of informed consent on patient decisions regarding third molar removal - GÖÇMEN, GÖKHAN; ATALI, ONUR (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2017)
Purpose: We investigated whether the order in which patients learned about complication risks affected their anxiety about and willingness to undergo the removal of their third molar. Materials and Methods: In total, 171 patients (65 males, 106 females) were included in the study. The distributions of gender and the position of mandibular third molars were recorded. The Amsterdam Preoperative Anxiety and Information Scale and Spielberger's State-Trait Anxiety Inventory were used to evaluate anxiety. Associations of anxiety with timing (pre/post), gender, and the order in which the information was presented in the consent form were analyzed. Results: The most common angulations were horizontal (26.3%) and mesioangular (60.2%), and these were more common in women. All patients obtained significantly higher anxiety scores after reading the consent form. There was no significant difference in anxiety scores, according to the order of information. In total, 88 patients underwent surgery, whereas 83 postponed the extraction after reading the consent form. Women were significantly more anxious than men before the procedure. Patients showed lower anxiety levels after the procedure (P < 0.05). Conclusion: Increased anxiety was not associated with the order in which information was presented in the informed consent form. However, the informed consent form itself was a major contributor to increased patient anxiety. Further studies regarding the contents of consent forms and their effects on patient anxiety and decisions regarding third molar removal are needed.
Keywords: Anxiety; informed consent; third molar extraction; INFORMATION; SURGERY; ANXIETY